1987
DOI: 10.1017/s0890037x0002933x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Atrazine Residue on Soybean Growth Under Three Tillage Systems and Various Herbicides

Abstract: Field experiments were conducted to examine the effect of tillage on atrazine [6-chloro-N-ethyl-N′-(1-methylethyl)-1,3,5-triazine-2,4-diamine] persistence in the soil and soybean [Glycine max(L.) Merr.] injury. Tillage systems evaluated were no-tillage, chisel plowing, and moldboard plowing. Reduced tillage systems, such as no-tillage or chisel plowing, resulted in greater soybean injury from atrazine residue than did moldboard plowing. Regardless of atrazine residue level, metribuzin [4-amino-6-(1,1-dimethyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

1990
1990
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…Previous field studies have found a generally positive association between amphibian helminth infections and agricultural activity (e.g., Koprivnikar et al, 2006;Rohr et al, 2008b;King et al, 2010); but again, these studies mainly focused on the presence of the herbicide atrazine (typically associated with corn crops). By focusing on ponds adjacent to soybean fields, a crop for which atrazine is not applied (Pawlak et al, 1987), we decreased the chances that landscape factors were confounded with the presence of atrazine. Additionally, the glyphosatebased compounds (e.g., RoundupH, St. Louis, Missouri, USA) most often associated with soybean crops are now the most widely applied herbicides in the world (Struger et al, 2008) and have documented effects on aquatic vertebrate mortality and susceptibility to parasitism in laboratory experiments (e.g., Rohr et al, 2008a;Kelly et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Previous field studies have found a generally positive association between amphibian helminth infections and agricultural activity (e.g., Koprivnikar et al, 2006;Rohr et al, 2008b;King et al, 2010); but again, these studies mainly focused on the presence of the herbicide atrazine (typically associated with corn crops). By focusing on ponds adjacent to soybean fields, a crop for which atrazine is not applied (Pawlak et al, 1987), we decreased the chances that landscape factors were confounded with the presence of atrazine. Additionally, the glyphosatebased compounds (e.g., RoundupH, St. Louis, Missouri, USA) most often associated with soybean crops are now the most widely applied herbicides in the world (Struger et al, 2008) and have documented effects on aquatic vertebrate mortality and susceptibility to parasitism in laboratory experiments (e.g., Rohr et al, 2008a;Kelly et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several environmental factors, including soil pH (15)(16)(17), temperature (18), and moisture (79), tillage practices (17,(20)(21)(22) and other soil properties (23) have been shown to influence atrazine persistence in soils. Degradation by microorganisms (24)(25)(26)(27)(28)(29)(30)(31)(32)(33) reduces atrazine concentrations in soil.…”
Section: Atrazine Degradationmentioning
confidence: 99%
“…Injury from clomazone residues to a sensitive rota tional crop also may be affected by tillage used to prepare a seedbed for the rotational crop. Moldboard plowing may dilute clomazone residues sufficiently to avert crop injury, as has been reported for certain other herbicides (3,14). On the other hand, the low leaching potential of clomazone in most soils (12,21) suggests that tillage may place the herbicide deeper in the soil profile than would occur in the absence of tillage.…”
mentioning
confidence: 91%